Selected anionic and cationic surface active agents: case study on the Kłodnica sediments - Olkowska Ewa; Ruman Marek; Drąg-Śmigalska Magdalena; Polkowska Żaneta (Limnological Review, 2017)
Surface active agents (surfactants) are a group of chemical compounds, which are used as ingredients of detergents, cleaning products, cosmetics and functional products. After use, wastes containing surfactants or their degradation products are discharged to wastewater treatment plants or directly into surface waters. Due to their specific properties of SAAs, compounds are able to migrate between different environmental compartments such as soil, sediment, water or even living organisms and accumulate there. Surfactants can have a harmful effect on living organisms. They can connect with bioactive molecules and modify their function. Additionally, they have the ability to migrate into cells and cause their damage or death. For these reasons investigation of individual surfactants should be conducted. The presented research has been undertaken to obtain information about SAA contamination of sediment from the River Kłodnica catchment caused by selected anionic (linear alkylbenzene sulfonates (LAS C10-C13)) and cationic (alkylbenzyldimethylammonium (BDMA-C12-16), alkyl trimethyl ammonium (DTMA), hexadecyl piridinium chloride (HP) chlorides) surfactants. This river flows through an area of the Upper Silesia Industrial Region where various companies and other institutions (e.g. coal mining, power plants, metallurgy, hospitals) are located. To determine their concentration the following analytical tools have been applied: accelerated solvent extraction– solid phase extraction – high performance liquid chromatography – UV-Vis (anionic SAAs) and conductivity (cationic SAAs) detectors. In all sediments anionic SAAs have been detected. The concentrations of HTMA and BDMA-C16 in tested samples were higher than other cationic analytes. Generally, levels of surfactants with longer alkyl chains were higher and this observation can confirm their higher susceptibility to sorption on solid surfaces.